2018
DOI: 10.1364/boe.9.002095
|View full text |Cite
|
Sign up to set email alerts
|

Selective delivery of laser energy to ester bonds of triacylglycerol in lipid droplets of adipocyte using a quantum cascade laser

Abstract: The recent development of quantum cascade lasers (QCLs) has facilitated the irradiation of a mid-infrared laser beam that is specifically absorbed by a target molecular bond. Aiming for a selective delivery of laser energy to a specific absorption at 1,738 cm by the ester bonds of triacylglycerol (TAG), a QCL beam with a wavenumber of 1,710 cm was irradiated to 3T3-L1 adipocytes and preadipocytes. Neutral red staining, and FITC-labeled annexin V and ethidium homodimer-III assays revealed the occurrence of adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Immature and mature adipocytes have substantially different light absorption properties [61]. Absorption spectra obtained with FTIR spectrometry in 3T3-L1 preadipocytes and corresponding mature adipocytes revealed that light absorption in some wavelength intervals was much higher in preadipocytes than in the corresponding mature adipocytes.…”
Section: Selective Modification Of Immature and Mature Adipocytes By mentioning
confidence: 95%
“…Immature and mature adipocytes have substantially different light absorption properties [61]. Absorption spectra obtained with FTIR spectrometry in 3T3-L1 preadipocytes and corresponding mature adipocytes revealed that light absorption in some wavelength intervals was much higher in preadipocytes than in the corresponding mature adipocytes.…”
Section: Selective Modification Of Immature and Mature Adipocytes By mentioning
confidence: 95%
“…However, one of the urgent problems of aesthetic surgery, which is to develop an effective and safe method of removing unwanted fat, remains unresolved. There are many contemporary wave‐based methods of fat cell lipolysis and liposuction, such as ultrasonic , radiofrequency and laser technologies. The wave method is associated with radiation in a certain range of wavelengths (frequencies), which is effectively absorbed by the tissue, that is, optical, microwave or ultrasonic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a MIR quantum cascade laser with the wavelength of 5847.9 nm was suggested for direct lipolysis of adipocytes . This radiation is absorbed specifically by a target molecular bond of lipids in adipocytes and preadipocytes and leads to cell apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%